The feasibility of evaluating a tobacco control intervention for working youth. (26th November 2003) - Fagan, P; Stoddard, A M; Hunt, M K; Frazier, L; Girod, K; Sorensen, G
Abstract : Objectives: To describe the feasibility of implementing evaluation methods for a worksite tobacco control intervention for teens. Indicators of feasibility included employment stability, response rates to multiple surveys, and self reported 30 day smoking. Design: Grocery stores that were part of a single chain were randomised to four intervention stores and five control stores as part of the SMART project, a phase II methods development study designed to reduce smoking among working adolescents. Subjects: Data on smoking in the last 30 days and employment patterns were collected from working teens aged 15–18 years at seven data points over the 12 month intervention period using cross sectional surveys. Results: Data on employment stability indicate that employee turnover rates averaged 21% over the seven administrations. Response rates for the seven surveys ranged from 43–77% and were slightly greater in the control stores than the interventions stores (71% v 59%, p = 0.06). Mean current smoking at the individual store level ranged from 9–32% and there was a negative correlation between smoking prevalence and response rate by survey and by store (–0.029, p = 0.03). Among smokers who completed at least two surveys, there were no significant differences between intervention and control store on changes in the frequency of smoking. Conclusions: Evaluating a tobacco control intervention in the grocery store setting requires multiple survey assessments to monitor changes in smoking among adolescents. Strategies are needed to maintain high response rates and increase the number of multiple responses from eligible teens.